DETERMINAN PERTUMBUHAN KREDIT KONSUMSI PADA BANK UMUM DI INDONESIA - Nirma Handayani La'ia (2023)
This research was conducted to determine the effect of Third Party Funds, Non Performing Loans, interest rates and inflation on the growth of consumer credit at commercial banks. This research uses 20 commercial banks that are classified as BUKU III and IV consistently during 2015-2020, so that the total sample is 120 data. The data used is secondary data sourced from the Banking Consolidated Annual Report. The hypothesis testing in this study used panel data regression analysis with the STATA 17 program. The results showed that partially NPLs and inflation had an effect on consumption credit, while DPK and interest rates had no effect on consumption credit growth. The results also show that simultaneously the four independent variables influence the growth of consumption credit.